Penerapan Model Pembelajaran Team Games Tournament untuk Meningkatkan Hasil Pembelajaran Menganalisis Unsur Intrinsik Cerita Pendek Siswa Kelas XI-D3 SMA Negeri 9 Surabaya - Yayuk Pundy Astutik (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to improve students' learning outcomes in analyzing the intrinsic elements of short stories through the application of Team Games Tournament (TGT) learning model in class XI-D3 SMAN 9 Surabaya. This research was conducted in two cycles, with each cycle including four stages: planning, action, observation, and reflection. Data were collected through classroom observation, field notes, learning outcome tests, and analysis of intrinsic elements of short stories by students. The results showed that the application of the TGT learning model was effective in improving students' learning outcomes in analyzing the intrinsic elements of short stories. This improvement can be seen from the increase in students' test scores from cycle 1 to cycle 2. This study suggests that the TGT learning model can be used as an effective alternative learning strategy to improve students' learning outcomes in analyzing the intrinsic elements of short stories. In addition, this study also shows that short stories are the right learning media to develop students' analytical skills.